INDIGENOUS PLANT-DERIVED MEDICINE USED BY ORDINARY COMMUNITY MEMBERS OTHER THAN TRADITIONAL HEALTH PRACTITIONERS FOR PREVENTIVE HEALTH CARE IN MOHLALETSI COMMUNITY IN LIMPOPO PROVINCE, SOUTH AFRICA - Agnes Rankoana, Sejabaledi (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Research on medical ethnobotany shows that ordinary community members in the rural areas have knowledge of selfpreventivecare which is accomplished through administration of plant medicine to prevent the onset of disease and create a sense ofwell-being. Several medicinal plants and traditional medicines derived from them have been used to enhance resistance to severaldisease agents. The present study documented the indigenous plant-derived medicines used by Mohlaletsi community members tominimize the chances of contracting disease thus promoting good health and well-being.Materials and Methods: Structured interviews were used to collect data among 80 respondents purposely sampled to shareknowledge about the use of indigenous plant-derived medicine for preventive health care.Results: The results of the study revealed six indigenous plant species belonging to six families identified as sources of medicineadministered for preventive care of primary health care. Preventive medicine is prepared from the mixture of plant partsadministered to limit susceptibility to disease and improve the general well-being. The medicine is repeatedly reported to promotegood health and well-being of the children by limiting the children’s vulnerability to disease and promote their welfare.Conclusion: Ordinary community members use plant-derived medicine to prevent attack by disease in an effort to promote goodhealth and well-being. This type of preventive care may form the basis for community participation towards the achievement ofprimary health care needs in the rural areas.